Pembinaan Kesehatan Mental Remaja sebagai Upaya Preventif di Desa Gunung Geulis: Pendekatan Berbasis Komunitas - Hakim, Ibrahim al; Suci Siti Lathifah; Noor, Keysha Alea Zahranzani; Wahyuni, Dwi Sri; Nurjanah, Alifia Siti; Almahdi, M. Haikal (CV. Dharma Samakta Edukhatulistiwa, 2025)
The issue of adolescent mental health in Gunung Geulis Village is of significant concern, given the elevated stress levels and dearth of emotional support experienced by local adolescents. A gap exists in the literature that reflects a discrepancy between mental health theory and field practice, particularly the absence of effective community-based programmes. The objective of this service programme is to enhance emotional competencies, social support networks, and mental health literacy among adolescents, while concurrently reducing the stigma associated with mental illness. The programme employs a range of methods, including emotional skills training, the formation of peer support groups, socio-cultural activities, and counselling for parents and teachers. The strategy is designed to bridge the gap between theory and practice through a community-based approach that engages various stakeholders. The results of the programme demonstrated a notable reduction in adolescent stress levels from 70% to 30%, an improvement in emotion management skills in 90% of participants, and an increase in social support and a sense of community. These key findings highlight the efficacy of the community-based approach in enhancing adolescents' psychological well-being. In conclusion, the programme has successfully bridged the gap between theory and practice, demonstrating that community-based interventions are effective in addressing mental health issues. The findings provide a basis for the implementation of similar programmes in other communities and the development of more comprehensive mental health policies.